Criminal Liability For Those Who Enter Into Contract Marriages With Minors In Indramayu Regency - Harits Tirta Rofif; Sanusi; Muhamad Noupel (International Journal Labs, 2026)
The practice of contract marriage (mut'ah marriage) involving minors is a socio-legal phenomenon that persists in Indramayu Regency and raises serious problems from a criminal law perspective. This study aims to analyze the factors hindering law enforcement and examine the forms of legal accountability for perpetrators. The method used is normative legal research with a statutory, conceptual, and case-based approach. The results indicate that obstacles to law enforcement are influenced by permissive socio-cultural factors, community economic conditions, low legal awareness, and the practice being conducted behind closed doors and involving family members or intermediaries. Legally, contract marriage lacks legal legitimacy and, if it involves children, is classified as a criminal act of sexual exploitation, punishable by the Child Protection Law, the TPKS Law, and the provisions of the Criminal Code. The perpetrator's criminal liability is based on intent and cannot be waived by reason of the child's consent. Furthermore, participating parties can be held accountable based on the concept of participation. Therefore, firm law enforcement and a preventative approach are needed to provide maximum protection for child victims